AB0117 HOMOCYSTEINYLATED ALPHA 1 ANTI-TRYPSIN AS A POTENTIAL ANTIGENIC TARGET IN RHEUMATOID ARTHRITIS. (June 2019) - Colasanti, Tania; Sabatinelli, Danilo; Mancone, Carmine; Pecani, Arbi; Speziali, Mariangela; Vomero, Marta; Barbati, Cristiana; Celia, Alessandra Ida; Finucci, Annacarla; Perricone, Carlo; Ceccarelli, Fulvia; Spinelli, Francesca; et al.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic, inflammatory, autoimmune disorder that primarily affects joints. Beside the well-known rheumatoid factor (RF) and anti-citrullinated protein antibodies (ACPA) have been reported to be a very useful diagnostic and prognostic marker of RA, recently antibodies against carbamylated proteins (anti-CarP) have been described also in ACPA negative RA patients. However, more than 20% of RA cases are still defined as seronegative forms. Therefore, the individuation of new antibody specificities in RA could be helpful for diagnostic and prognostic purposes. Objectives: The goals of this study were the identification and the immunologic characterization of post-translational modified synovial fluid (SF) autoantigens, specifically targeted by autoantibodies from sera of seronegative RA patients. Methods: SFs from 5 seronegative RA patients were collected, pooled and treated with hyaluronidase. After removal of both albumin and IgG, the sample was washed and cleansed, concentrated, separated by 2-dimensional electrophoresis (2-DE) and then transferred by Western blotting to nitrocellulose membrane, for autoantigen detection by immunoassay, using a pool of sera from 5 seronegative RA patients. The antigenic protein spots were identified by peptide mass fingerprint, using a Matrix-Assisted Laser Desorption/Ionization-Time Of Flight (MALDI-TOF) mass spectrometer. This approach revealed Alpha 1 Anti-Trypsin (A1AT) as a target of RA patients autoantibodies. Pooled SFs were also analyzed by reverse-phase nanoliquid chromatography and tandem mass spectrometry, to confirm the presence of A1AT and for the identification of A1AT post-translational modifications. Homocysteinylated A1AT was immunoprecipitated from pooled SFs of RA seronegative patients and, after a diafiltration and concentration process, was used as an antigen to detect anti-homocysteinylated A1AT antibodies by Enzyme-Linked ImmunoSorbent Assay (ELISA). In order to this, consecutive patients with RA, osteoarthritis (OA), psoriatic arthritis (PsA), and healthy donors were enrolled and sera were collected. Results: Homocysteinylated A1AT was identified as a potential antigenic target not only in ACPA and RF positive RA patients but, more importantly, also in RA seronegative patients. Antibodies anti-homocysteinylated A1AT were found in 66.7% (44/66) RA patients seronegative for ACPA and RF, 88.6% (39/44) RA patients, 15% (3/20) OA patients, 26.3% (5/19) PsA patients and in none (0/41) of healthy donors. Conclusion: Homocysteinylated A1AT was identified as a new possible antigenic target of autoantibodies in sera from RA patients, including RA seronegative patients. This tool may be useful in diagnosis and monitoring of the disease and may contribute to understand the immunopathogenic mechanisms of RA in future studies. Disclosure of Interests: Tania Colasanti: None declared, Danilo Sabatinelli: None declared, Carmine Mancone: None declared, Arbi Pecani: None declared, Mariangela Speziali: None declared, Marta Vomero: None declared, cristiana barbati: None declared, Alessandra Ida Celia: None declared, Annacarla Finucci: None declared, Carlo Perricone Speakers bureau: BMS; Lilly, Celgene, Sanofi, Fulvia Ceccarelli: None declared, francesca spinelli: None declared, Vincenzo Barnaba: None declared, fabrizio conti: None declared, Guido Valesini: None declared, cristiano alessandri: None declared